Cardioprotective Effect of High Intensity Interval Training and Nitric Oxide Metabolites (NO2-, NO3-) - Aliasghar FALLAHI; Abbasali GAEINI; Shahnaz SHEKARFROUSH; Ali KHOSHBATEN (Tehran University of Medical Sciences, 2015)
Background: The aim of this study was to investigate the effects of High-Intensity Interval Training (HIIT) on nitric oxide metabolites (NO2-, NO3-) and myocardial infarct size after Ischemia/Reperfusion (I/R) injury in healthy male rats. Methods: A total of 44 Wistar rats were randomly divided into 4 groups including HIIT (n=8), HIIT + IR protocol (n=14), control (n=8), and control + IR (n=14). Each training session of HIIT consisted of 1 hour of exercise in three stages: 6-minute running at 50-60% VO2max for warm-up; 7 intervals of 7-minute running on treadmill with a slope of 50 to 20° (4 minutes with an intensity of 80-100% VO2max and 3 minutes at 50-60% VO2max); and 5-minute running at 50-60% VO2max for cool-down. The control group did not participate in any exercise program. Nitric Oxide (NO) and its metabolites were measured by using Griess reaction test.   Results: The results showed that eight weeks of exercise training exerted a significantly increasing effect on nitrite (8.55 µmol per liter, equivalent to 34.79%), nitrate (62.02 µmol per liter, equivalent to 149.48%), and NOx (66 µmol per liter, equivalent to 98.11%) in the HIIT group compared with the control group. The results showed myocardial infract size (IS) was significantly smaller (23.2%, P<0.001) in the exercise training group compared with the control group. Conclusion: Incremental changes in NO-NO3-, NO2- axis are one of mechanisms through which HIIT program can protect the heart from I/R injury and decrease myocardial infarction.